A Genetic Algorithm Based Method for Molecular Docking - Li, Chun-lian; Sun, Yu; Long, Dong-yun; Wang, Xi-cheng (Advances in Natural Computation, 2005)
The essential of Molecular docking problem is to find the optimum conformation of ligand bound with the receptor at its active site. Most cases the optimum conformation has the lowest interaction energy. So the molecular docking problem can be treated as a minimization problem. An entropy-based evolution model for molecular docking is proposed in this paper. The model of molecular docking is based on a multi-population genetic algorithm. Two molecular docking processes are investigated to demonstrate the efficiency of the proposed model.